Sales location and supply response among semisubsistence farmers in Benin: A heteroskedastic double selection model - Takeshima, Hiroyuki; Winter-Nelson, Alex (International Food Policy Research Institute, 2010)
In much of rural Africa, high transaction costs limit farmers' market participation and thus their potential for income growth. Transaction costs can affect not only whether a farmer sells product but also whether sales occur at the farm gate on at a market. If production behavior is related to a chosen sales location, then analysis of interventions can be improved by explicit consideration of the decision of where to sell. This paper develops a double-selection model that explains consumption and production decisions by semi-subsistence farmers who first decide whether to be a seller and then whether to sell at the farm gate or at an off-farm location before deciding on production and consumption. The study tests the validity of this dual-criteria model against a single criterion model in which a grower first decides to be a seller and then decides production, consumption and sales location simultaneously. Dual-criteria and single-criterion models are compared while correcting inconsistency in estimations due to violation of homoskedasticity and normality assumptions in selection equations. The results suggest that the dual-criteria model provides more information than the single-criterion model using a sample of cassava producer in Benin.